Application of Human Placental Villous Tissue Explants to Study ABC Transporter Mediated Efflux of 2,4-Dinitrophenyl-S-Glutathione - S. Vaidya, Soniya; W. Walsh, Scott; M. Gerk, Phillip (Current Pharmaceutical Biotechnology, 2011)
Objective: The purpose of this study was to characterize the human term placental villous tissue explant culture model as a tool to study the formation and efflux of 1-chloro-2,4-dinitrobenzene (CDNB) conjugate 2,4-dinitrophenyl-Sglutathione (DNP-SG) as a model system for phase II metabolism and ATP-binding cassette (ABC) transporter-mediated cellular efflux. Methods: Placental tissue samples were obtained after cesarean section following normal pregnancies (n=9). Cultured villous tissue was monitored up to 48 h to study the effect of time in culture on biochemical parameters, formation and efflux of DNP-SG in the absence or presence of ATPase inhibitor sodium orthovanadate and the protein expression of ABC transporters - multidrug resistance associated protein 2 (MRP2), P-glycoprotein (P-gp), breast cancer resistance protein (BCRP), and enzyme glutathione-S-transferase isoform P1-1 (GSTP1-1). Results: Villous tissue structure, tissue viability and expression of BCRP, GSTP1-1 remained unchanged, while expression of MRP2, P-gp and total tissue glutathione decreased with time in culture. Tissue integrity was unchanged up to 24 h but declined at 48 h. However, DNP-SG formation, DNP-SG efflux, and the extent of inhibition of DNP-SG efflux by sodium orthovanadate showed only minor changes through 48 h. Sodium orthovanadate decreased DNP-SG efflux, consistent with inhibition of apical ABC transporters. Conclusion: The results support the use of the cultured human term placental villous tissue explants model to study the coordinated function of GSTP1-1 and apical ABC transporters in the formation and efflux of the model substrate DNP-SG.
Keywords: placental explants culture